HUBUNGAN KOMPETENSI KEAHLIAN DENGAN BIDANG PEKERJAAN ALUMNI PROGRAM STUDI TEKNIK SIPIL UNIVERSITAS NEGERI SURABAYA - Meity Wulandari; Yogie Risdianto; Danayanti Azmi Dewi Nusantara; Mochamad Firmansyah Sofianto; Alwan Gangsar Brilian Putra (LPPM Universitas Negeri Jakarta, 2025)
Tracing the relationship of expertise competence to the field of work of Civil Engineering S1 alumni of Universitas Negeri Surabaya (UNESA) with the Tracer Study method in the form of filling out questionnaires by graduates aims to obtain information about the types of stakeholders as users of graduates; information related to the suitability between disciplines and the field of work chosen by graduates; and to determine the competence of graduates against the needs of industry or the world of work based on data analysed by quantitative descriptive methods. The results of the analysis show that 82% of graduates work in the construction field and 18% in the non-construction field, which percentage interprets that the discipline of civil engineering competence at UNESA is relevant to the field of work being undertaken by graduates and the competence of graduates who have been indicated in accordance with the needs of industry and the world of work based on the percentage of alumni data who have worked greater than alumni who have not worked, namely 73% of alumni have worked in 2022 graduates, 64% have worked in 2023 graduates, and in 2024 graduates, 87% of alumni have worked.